1981
DOI: 10.1007/bf00429211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine on two types of motor activity in rats

Abstract: Effects of injections of two doses of nicotine (o.2 and 0.4 mg/kg body wt) were tested on general activity (in a photocell chamber) and on locomotor activity (in an activity wheel) in male and female rats of two ages (40 and 90 days). Behavior was monitored under light and dark conditions at 15, 30, and 45 min post-injection over a period of 12 days. A general excitatory effect of nicotine was observed in the photocell chamber, with the high dosage greatly increasing activity for younger and female animals. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Voluntary exercise (and wheel running, its homologous in rodents) is considered a form of reinforcement (Garland et al, 2011). Nicotine markedly increases wheel running in rats habituated to the cage for several hours postinjection (Bryson, Biner, McNair, Bergondy, & Abrams, 1981;Gillman et al, 2008; but see Kuribara, Shinoda, & Uchihashi, 1995 for different effects in mice). When nicotine is administered chronically at fixed times of the day, increased wheel running is observed in the preinjection phase and persists for at least two days after cessation of the treatment (Gillman et al, 2008).…”
Section: Nicotine Effects On Central Circuits Of the Reward Systemmentioning
confidence: 99%
“…Voluntary exercise (and wheel running, its homologous in rodents) is considered a form of reinforcement (Garland et al, 2011). Nicotine markedly increases wheel running in rats habituated to the cage for several hours postinjection (Bryson, Biner, McNair, Bergondy, & Abrams, 1981;Gillman et al, 2008; but see Kuribara, Shinoda, & Uchihashi, 1995 for different effects in mice). When nicotine is administered chronically at fixed times of the day, increased wheel running is observed in the preinjection phase and persists for at least two days after cessation of the treatment (Gillman et al, 2008).…”
Section: Nicotine Effects On Central Circuits Of the Reward Systemmentioning
confidence: 99%
“…The effects of nicotine on locomotor activity depend critically on the behavioural measure used (Bryson et al, 1981). In our previous studies (Clarke & Kumar, 1983a,b), we investigated only gross horizontal locomotion.…”
Section: Introductionmentioning
confidence: 99%
“…However, the body weight results showed that NIC suppressed weight throughout the entire NIC administration phase. That body weight remained suppressed while food intake showed recovery may be due to NIC's ability to increase energy expenditure (Bryson et al 1981;Bowen et al 1986;Winders and Grunberg 1990).…”
Section: Discussionmentioning
confidence: 91%